Determinants of cross-national knowledge transfer and its effect on firm innovation - Kotabe, Masaaki; Dunlap-Hinkler, Denise; Parente, Ronaldo; Mishra, Harsh A (Journal of International Business Studies, 2007)
This study examines the determinants of international knowledge flow. From a resource-based perspective, it evaluates the impact of cross-national knowledge transfer on firm innovative performance. Based on 56,027 US patents owned by 53 selected firms in the US-based pharmaceutical industry, the results suggest that innovative performance is a curvilinear function of the international knowledge content used by a firm to innovate. As hypothesized, it was found that at (1) low and moderate levels of international knowledge content, a firm's strategy to transfer international knowledge improves its innovative performance, and at (2) higher levels of international knowledge content, there are diminishing marginal returns to transferring knowledge from overseas.